Genome‐wide association study identifies loci associated with liability to alcohol and drug dependence that is associated with variability in reward‐related ventral striatum activity in African‐ and European‐Americans. (11th June 2019) - Wetherill, Leah; Lai, Dongbing; Johnson, Emma C.; Anokhin, Andrey; Bauer, Lance; Bucholz, Kathleen K.; Dick, Danielle M.; Hariri, Ahmad R.; Hesselbrock, Victor; Kamarajan, Chella; Kramer, John; Kuperman, Samuel; et al.
Abstract: Genetic influences on alcohol and drug dependence partially overlap, however, specific loci underlying this overlap remain unclear. We conducted a genome‐wide association study (GWAS) of a phenotype representing alcohol or illicit drug dependence ( ANYDEP ) among 7291 European‐Americans (EA; 2927 cases) and 3132 African‐Americans (AA: 1315 cases) participating in the family‐based Collaborative Study on the Genetics of Alcoholism. ANYDEP was heritable ( h 2 in EA = 0.60, AA = 0.37). The AA GWAS identified three regions with genome‐wide significant (GWS; P < 5E‐08) single nucleotide polymorphisms (SNPs) on chromosomes 3 (rs34066662, rs58801820) and 13 (rs75168521, rs78886294), and an insertion‐deletion on chromosome 5 (chr5:141988181). No polymorphisms reached GWS in the EA. One GWS region (chromosome 1: rs1890881) emerged from a trans‐ancestral meta‐analysis (EA + AA) of ANYDEP, and was attributable to alcohol dependence in both samples. Four genes (AA: CRKL, DZIP3, SBK3 ; EA: P2RX6 ) and four sets of genes were significantly enriched within biological pathways for hemostasis and signal transduction. GWS signals did not replicate in two independent samples but there was weak evidence for association between rs1890881 and alcohol intake in the UK Biobank. Among 118 AA and 481 EA individuals from the Duke Neurogenetics Study, rs75168521 and rs1890881 genotypes were associated with variability in reward‐related ventral striatum activation. This study identified novel loci for substance dependence and provides preliminary evidence that these variants are also associated with individual differences in neural reward reactivity. Gene discovery efforts in non‐European samples with distinct patterns of substance use may lead to the identification of novel ancestry‐specific genetic markers of risk. Abstract : We conducted a genome‐wide association study (GWAS) of a phenotype (ANYDEP) representing dependence on alcohol or any illicit drug. ANYDEP was heritable in European American (EA: 60%) and African American (AA: 37%) families. In the AA GWAS, we identified novel loci on chromosomes 3, 5 and 13, attributable to contributions from each illicit drug and alcohol. A locus on chromosome 1 emerged in the trans‐ancestral (EA+AA) GWAS and was not associated with ANYDEP after excluding individuals with alcohol dependence alone, indicating that this finding was attributable to alcohol dependence alone. The chromosome 1 and 3 variants were associated with ventral striatal activation in an independent sample. Results provide preliminary evidence for loci that influence liability to addiction via reward‐related pathways.